Pengaruh Disiplin Kerja dan Kompensasi terhadap Kepuasan Kerja Pegawai pada Biro Organisasi dan Sumber Daya Manusia Aparatur Kementerian Pertanian - Husnah Gustiyaningsih; Ratnawaty Marginingsih; Wiwit Rohaeni Yulianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of work discipline and compensation on employee job satisfaction at the Bureau of Organization and Human Resources of the Ministry of Agriculture. This research is motivated by the importance of proper work discipline and compensation in increasing employee job satisfaction. The method used in this research is quantitative method with descriptive approach. The data collection technique was carried out through distributing questionnaires to 85 respondents who were employees of the agency. The data analysis technique uses validity, reliability, multiple linear regression, t test, f test, and the coefficient of determination. The results of this study obtained using the t test that work discipline partially has a positive and significant effect on employee job satisfaction with a significance result of 0.000 <0.05 and the t test results show Tcount 3.656> Ttable 1.989. Compensation partially has a positive and significant effect on employee job satisfaction with a significance result of 0.000 < 0.05 and the t test results show Tcount 7.066 > Ttable 1.989. Work discipline and compensation simultaneously have a positive and significant effect on employee job satisfaction with a significance result of 0.000 < 0.05 and the f test results show Fcount of 62.960> Ftable 3.11. The coefficient of determination test found that the two independent variables had an effect of 60.6% on employee job satisfaction.